Digital cashless payments and economic growth: evidence from CPMI countries - Yi, Xun Pang; Sin, Huei Ng; Wei, Theng Lau (Malaysian Finance Association, 2022)
Research Question: This paper aims to investigate the relationships between digital payments and economic growth in 27 CPMI countries. Besides, it also studies the comparison of the impacts of digital payments between developed and developing countries. Motivation: Digital cashless payments have been widely discussed in recent years and the penetration of cashless payments around the globe is rising exponentially throughout the decade. Several studies have found that cashless payments have a positive impact on economic growth. However, the existing studies are mainly focusing on the European countries. Committee on Payments and Market Infrastructures (CPMI) is a new area to be explored because it consists of some countries that are seldom being investigated in the related fields previously. Idea: Analysis consists of GDP growth as the variable of interest and transaction volumes of debit cards, credit cards and e-money payments as the explanatory variables. Several control variables are used to capture other effects in the model. Data: Data are collected from various sources of database for the period of 2013-2019 covering a total of 27 countries/regions which consist of 18 developed countries and 9 developing countries in the CPMI membership. Method/Tools: This paper employs a fixed effect panel data model to analyse the relationship between digital payments and economic growth in (1) all CPMI countries, (2) developed CPMI countries, (3) developing CPMI countries. A comparative analysis is also performed between the developed and developing CPMI countries. Findings: Our findings are in line with the expectation, where all three digital payments are positively correlated to economic growth. However, only the e-money payment is statistically significant to the economic growth. Besides, the findings also indicate that the effects of digital payments on the developed economies are greater than the developing economies. Contributions: CPMI members have put in considerable efforts in facilitating cashless payments. The analysis of the relationship between digital cashless payments and economic growth in CPMI countries provides a review on the effectiveness of the initiatives taken by the member countries. Our findings are expected to offer some new insights related to digital cashless payments and contribute to the modern financial sector.